STAGES OF DEVELOPMENT OF A TEACHER’S PROFESSIONAL FORMATION, AS A RESULT OF ITS CREATIVE PEDAGOGICAL ACTIVITY - B, Narzikulova F.; I.A, Raimkulova; G.N., 3Shadibaeva; K, Yakubjanova M. (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the stages of the teacher’s professional development in the process of his creative pedagogical activity. The article reveals the structure of professionalism of teacher’s pedagogical activity in three main components: professionalism of knowledge, professionalism of communication, and professionalism of self-improvement. The article presents the structure of professionally personal qualities of a teacher, the socio-pedagogical concept of teacher’s professional development and the stages of teacher’s professional development in the formation of a professional pedagogical image.